Effect of early hydration temperature on hydration product and strength development of magnesium phosphate cement (MPC). (December 2015) - You, Chao; Qian, Jueshi; Qin, Jihui; Wang, Hongtao; Wang, Qingzhen; Ye, Ziqi
Abstract: This paper investigates the effect of early hydration temperatures on hydration products and strength development of magnesium phosphate cement (MPC). MPC paste specimens with borate contents of 3%, 6%, 9% and 12% are prepared and cured in different air temperatures and in the adiabatic condition. The internal hydration temperatures are measured by pre-embedded temperature probes. MPC samples with different hydration temperatures are also obtained by using thin slice samples. The hydration products in MPC samples with different hydration temperatures are analyzed by X-ray diffractometer (XRD) and scanning electron microscope (SEM) and the strength development is also measured. The results show that NH4 MgPO4 ·6H2 O is the major hydration product and beneficial to strength development of MPC at hydration temperature below 70 °C. NH4 MgPO4 ·H2 O is another major product, which significantly decreases the strength, when the temperature is higher than a critical temperature between 70 °C and 75 °C. NH4 MgPO4 ·H2 O can directly form in the MPC paste, and comes from the decomposition of NH4 MgPO4 ·6H2 O when the temperature is above 75 °C. With temperature elevation and duration extension, NH4 MgPO4 ·6H2 O decomposes rapidly, and even entirely when the temperature is above 100 °C. The borate content has no effect on the types of major hydration products and the critical temperature.